Solve for t -15=2t-11

Math
-15=2t-11
Rewrite the equation as 2t-11=-15.
2t-11=-15
Move all terms not containing t to the right side of the equation.
Tap for more steps…
Add 11 to both sides of the equation.
2t=-15+11
Add -15 and 11.
2t=-4
2t=-4
Divide each term by 2 and simplify.
Tap for more steps…
Divide each term in 2t=-4 by 2.
2t2=-42
Cancel the common factor of 2.
Tap for more steps…
Cancel the common factor.
2t2=-42
Divide t by 1.
t=-42
t=-42
Divide -4 by 2.
t=-2
t=-2
Solve for t -15=2t-11

Download our
App from the store

Create a High Performed UI/UX Design from a Silicon Valley.

Scroll to top